Stimulated Raman Histology for Rapid Intra‐Operative Diagnosis of Sinonasal and Skull Base Tumors. (30th May 2022) - Fitzgerald, Conall W.R.; Dogan, Snjezana; Bou‐Nassif, Rabih; Mclean, Tim; Woods, Robbie; Cracchiolo, Jennifer R.; Ganly, Ian; Tabar, Viviane; Cohen, Marc A.
Abstract : Objective: Intra‐operative stimulated Raman histology (SRH) is a novel technology that uses laser spectroscopy and color‐matching algorithms to create images similar to the formalin‐fixed paraffin‐embedded (FFPE) section. We aim to assess the accuracy of SRH in a novel range of sinonasal and skull base tumors. Methods: Select patients undergoing sinonasal and skull base surgery using the Invenio Imaging™ Nio™ Laser Imaging SRH system between June 2020 and September 2021 were assessed. The SRH images were reviewed for pathologic features similar to frozen section (FS) and FFPE. Time taken for results and diagnostic concordance was assessed. Results: Sixty‐seven SRH images from 7 tumor types in 12 patients were assessed. Pathologies included squamous cell carcinoma, rhabdomyosarcoma, inverted papilloma, adenoid cystic carcinoma, SMARCB1‐deficient sinonasal carcinoma, mucosal melanoma, metastatic colonic adenocarcinoma, and meningioma. Tumor was identified in 100% of lesional specimens, with characteristic diagnostic features readily appreciable on SRH. Median time for diagnosis was significantly faster for SRH (4.3 min) versus FS (44.5 min; p = <.0001). Where SRH sample site matched precisely to FS ( n  = 32/67, 47.8%), the same diagnosis was confirmed in 93.8%. Sensitivity, specificity, precision, and overall accuracy of SRH were 93.3%, 94.1%, 93.8%, and 93.3%, respectively. Near‐perfect concordance was seen between SRH and FS (Cohen's kappa [κ] = 0.89). Conclusion: Stimulated Raman histology can rapidly produce images similar to FFPE H&E in sinonasal and skull base tumors. This technology has the potential to act as an adjunct or alternative to standard FS. Level of Evidence: 4 Laryngoscope, 132:2142–2147, 2022